MHD viscous flow and heat transfer due to a permeable shrinking sheet with prescribed surface heat flux - Md. Ali, Fadzilah; Mohd Nazar, Roslinda; Md. Arifin, Norihan (WSEAS Press, 2010)
In this paper, the problem of magnetohydrodynamic (MHD) viscous flow and heat transfer induced by a shrinking sheet with prescribed surface heat flux is studied. The transformed nonlinear ordinary differential equations are solved via the finite-difference scheme known as the Keller-box method. Both two-dimensional and axisymmetric cases are considered. The results for the skin friction coefficient and wall temperature, velocity and temperature profiles are presented and discussed for various parameters.